Circle dance: integrative and complementary practice in the daily health promotion for older adults - Kelly Maciel da Silva; Rosane Gonçalves Nitschke; Michelle Kuntz Durand; Ivonete Teresinha Schülter Buss Heidemann; Adriana Dutra Tholl; Pamela Camila Fernandes Rumor; Maria Josefa Arcaya Moncada (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to understand circle dance as an integrative and complementary practice for health promotion in older adults' daily lives. Methods: an interpretive, qualitative study, based on Michel Maffesoli's Comprehensive Sociology of Everyday Life. There were 20 participants, 17 older adults and three focalizers in circles held in Basic Health Units in a municipality in southern Brazil. Data were collected through interviews and observation, between September 2016 and March 2017, and analyzed through preliminary analysis, ordering, key links, coding and categorization. Results: three categories emerged that express the daily life of circle dance with older adults: circles that spin; challenges for new circles to spin; entering, being and staying in the circle. Final Considerations: circle dance provided older adults with a feeling of belonging to a group, combined with pleasure and well-being, contributing to promotion of older adults' health.